Diseño e implementación de un sistema de control electrónico a través de un micro controlador con señales mioeléctricas para el mejoramiento de la movilidad de un prototipo de prótesis de antebrazo humano izquierdo. - Álvarez Caiza, Luis Eduardo (2019)
The technological proposal aims to design and implement an electronic control system through a microcontroller with myoelectric signals to improve the mobility of a left human forearm prosthesis. In Ecuador in 2018, approximately 7.30% of the population have disabilities of which 212,776 have physical disabilities, in this group they are considered people who have lost one or both upper limbs, many of them are of low economic resources for those to achieve a stable electronic control prosthesis with a considerable degree of functionality, they find it very expensive because these prostheses abroad exceed tens of thousands of dollars; This is why this technological proposal seeks to help people with low economic resources to have an electronic prosthesis of the left forearm to perform basic activities of daily life, allowing them to be inserted in a more inclusive way to society. The gForce 100 ARMBAND sensor was used to capture myoelectric signals, since it has the advantage of having non-invasive dry electrodes with a long service life, the methods were used: scientific, quantitative and experimental, while mechanical variables were used. determined the degrees of freedom, force and pressure analysis through Inventor together with Newton's laws, as well as for the electronic control the programming was carried out on the Arduino Nano card which receives the serial data of the gForce sensor for control of the micro servos for the generation of phalange and wrist movements of the prosthesis. As a result, an upper limb prosthesis was obtained with 8 degrees of freedom, composed of 2 degrees on each finger (thumb, index and ring finger). In addition, a contribution was made with the design of a mechanism to perform the flexion-extension movement of the wrist with 2 degrees of freedom and for the generation of movements linear servo micros were used, it was also determined that the prosthesis can perform the following grips: spherical, strength, tip, hook and precision. Its construction was carried out by 3D printing whose advantage is that only the necessary material is used to shape complex three- dimensional models, in addition to optimizing the construction time.